Floor finishes at ablution areas in Masjid Sultan Iskandar and Masjid Al-Bukhari in Johor, Malaysia / Zuhanis Atan and Izzat Anuar - Atan, Zuhanis; Anuar, Izzat (2019)
This research is to collect all the data about the flooring materials effect between the coefficients of the friction of consumer’s foot act against the floor surface. The purpose of this section is to understand the differences between porcelain tiles and pebble wash tiles which is used in ablution area of Masjid Sultan Iskandar at Bandar Dato’ Onn and Masjid Al-Bukhari at Senai. The possibilities in the selection of the materials of ablution area in relation to the consumer's movement must be to avoid slipping. This research also to study the problems of slipping among consumers especially senior citizens and knowing the type of suitable flooring materials for ablution area. A comparison study is the most suitable for this research for finding the accurate in indifference, the disadvantages, the workability and the appropriate design for the floor finishes between the coefficient and friction. The purpose of this research is to identify which type of floor surface that suitable to use at ablution area that can bring a good impact and reduce the risk of falling to the user especially senior citizens through the selection of floor finishes materials and how the difference materials that suitable for ablution area to avoid slipping